Toward a three-dimensional framework for omni-channel - Saghiri, Soroosh; Wilding, Richard D.; Mena, Carlos; Bourlakis, Michael (Elsevier, 2017)
The omni-channel, as an emerging trend in retail, aims to coordinate processes and technologies across supply and sales channels. The evolution of this concept is still nascent. This paper develops a conceptual framework for omni-channel systems, configured by three dimensions of channel stage, channel type and channel agent. Integration and visibility are also explored and discussed as the main enablers, which support the implementation of omni-channel framework. This research is built upon the empirical and secondary data. Multiple case studies and expert interview methods are employed for data collection to validate the recommended framework and to explore its applicability. The framework proposed, along with the key integration and visibility enablers identified for the omni-channel, can be applied to a wide range of retail supply chains. It helps managers to develop, run and monitor omni-channel systems; it may also serve as a stepping-stone for development of the literature on omni-channel systems.
Keywords: Omni-channel; Channel integration; Channel visibility; Retail; Supply chain